Masted structures in architecture James B. Harris and Kevin Pui-K Li - Harris, James B. (Butterworth Architecture new technology series, 1996)
This book is an essential guide for architects to the structural and constructional implications of masted forms in relation to space enclosure, patterns of loading and use of differing materials and techniques. This useful volume will enable architects and engineers to understand the origins, development and nature of masted structures and will provide a stimulating basis for future design.